2014
DOI: 10.1165/rcmb.2013-0166ma
|View full text |Cite
|
Sign up to set email alerts
|

Airway Contractility in the Precision-Cut Lung Slice after Cryopreservation

Abstract: An emerging tool in airway biology is the precision-cut lung slice (PCLS). Adoption of the PCLS as a model for assessing airway reactivity has been hampered by the limited time window within which tissues remain viable. Here we demonstrate that the PCLS can be frozen, stored long-term, and then thawed for later experimental use. Compared with the never-frozen murine PCLS, the frozenthawed PCLS shows metabolic activity that is decreased to an extent comparable to that observed in other cryopreserved tissues but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 46 publications
1
53
0
Order By: Relevance
“…There also appears to be a general decrease in cytokine production during cultivation indicating a change in the cell population or cell function within PCLS over time in culture. One potential way to overcome this physiological change would be to explore the use of cryopreservation as described in Rosner et al 27 Their results showed minimal cell death, mainly along the edges, but also some reduction in the metabolic activity of the tissue following a freeze-thaw cycle. However, further optimization of such a cryopreservation technique could help to practically address the short window of viability of PCLS in culture.…”
Section: Discussionmentioning
confidence: 99%
“…There also appears to be a general decrease in cytokine production during cultivation indicating a change in the cell population or cell function within PCLS over time in culture. One potential way to overcome this physiological change would be to explore the use of cryopreservation as described in Rosner et al 27 Their results showed minimal cell death, mainly along the edges, but also some reduction in the metabolic activity of the tissue following a freeze-thaw cycle. However, further optimization of such a cryopreservation technique could help to practically address the short window of viability of PCLS in culture.…”
Section: Discussionmentioning
confidence: 99%
“…PCLSs have been widely used for studies of airway contractility and mechanisms of airway hyperreactivity in asthma (4,5,9,15,22,23). Because airway contraction requires the coordinated activity of ASMCs, this multicellular response requires high rates of ASMC viability after cryopreservation.…”
Section: Contractile and Relaxant Responses Of Airways In Cryopreservmentioning
confidence: 99%
“…Cryopreservation has been reported to store live biological samples with varying success (7,8), and its application to mouse PCLSs (mPCLSs) was previously assessed (9). This study employed histology and phase-contrast imaging to show that the lung tissue integrity and agonist-induced airway contraction were retained in cryopreserved mPCLSs.…”
mentioning
confidence: 99%
“…Dose response curves for MCh (10 −9 –10 −3 M) were recorded, after which the airways were dilated using the bitter taste receptor agonist chloroquine (10 −3 M, Sigma-Aldrich). A nylon mesh and metal washer were used to fixate the lung slice, as described previously (Rosner et al, 2014). Lung slice images were captured in time-lapse (1 frame per 2 s) using a microscope (Eclipse, TS100; Nikon).…”
Section: Methodsmentioning
confidence: 99%